CONTROL OF ROBOTIC HAND SIMULATOR via HUMAN HAND MOTION ANALYSIS BASED ON EMG - Tasar, Beyda; Kaya, Turgay; Gultan, Arif (Ieee, 2014)
Powered hand prostheses with many degrees of freedom have been researching advanced and intelligent powered hand prostheses for prosthetics. Electromyography (EMG) is widely used to design prostheses for its benefit to get valuable information about the neuromuscular activity of a muscle. This paper suggests the real time tracking algorithm for human hand motion by processing the signals of surface EMG sensors attached on brachioradialis nmscle. The signals acquired by using surface EMG sensors are processed with preprocesing step and filtering noises out with a banchvith filter. The processed EMG signals are directly used for the motion generation of hand in real time simulator. The hand of simillator which designed MATLAB GUI, has fourteen degrees of freedom and complies with the desired flexion/extension motions of both the finger of human. The EMG signal recorded via EMG Arduino Shield, is a low-cost and adaptable system. The system yields quick responses and is being a valuable tool for biomedical research and development.
22nd IEEE Signal Processing and Communications Applications Conference (SIU) -- APR 23-25, 2014 -- Karadeniz Teknik Univ, Trabzon, TURKEY
Keywords: Electromyography; hand simulator; EMG; hand motion analysis